Simple and fast calculation algorithm for computer-generated hologram with wavefront recording plane - Shimobaba, Tomoyoshi; Masuda, Nobuyuki; Ito, Tomoyoshi (Optics letters, 2009)
We present a simple and fast calculation algorithm for a computer-generated hologram (CGH) by use of wavefront recording plane. The wavefront recording plane is placed between the object data and a CGH. When the wavefront recording plane is placed close to the object, the object light passes through a small region on the wave recording plane. The computational complexity for the object light is very small. We can obtain a CGH to execute diffraction calculation from the wavefront recording plane to the CGH. The computational complexity is constant. The total computational complexity is dramatically reduced in comparison with conventional CGH calculations.